Rollover Prevention System for Passenger Vehicle - Phuman Singh, A.S.; Safarudin, Mochamad; Sihombing, Haeryip (2010)
An active roll control using roll moment rejection algorithm based on 14 DOF full vehicle model is proposed in this paper. For tire model, the Magic Tire formula was used. The full vehicle model was simulated and compared with vehicle dynamics simulation software and validated using an instrumented experimental vehicle. The active roll control algorithm was then introduced to the vehicle model. Combined with PID control, the results were then simulated and analyzed. From the simulation, it was found that the algorithm can significantly reduce the roll angle and roll rate of the vehicle and eventually prevent the vehicle from rollover. The improvement of the roll motion also reduces the load transfer from the inner wheels to outer wheels and hence increases the road holding during cornering.